Climate change due to heat and drought stress can alter the physiology of Maratheftiko local Cyprian grapevine variety - Chrysargyris, Antonios; Xylia, Panayiota; Antoniou, Omiros; Tzortzakis, Nikos G. (My University, 2018)
The effect of climate change (CC) on viticulture in Europe is of great concern and several international and indigenous grapevine cultivars have been examined for their adaptation to CC. In this study we focused on the short-term effects of light and moderate drought stress (DS) as well as heat stress (HS) on physiological and biochemical stress markers in Maratheftiko cultivar. We showed that leaf photosynthetic rate was decreased with DS and HS after 8 and 20 days. The leaf stomatal conductance was decreased in the case of DS after 8 days, while no differences could be found due to HS. Total phenols and flavonoids content and antioxidant capacity (FRAP and ABTS) were increased and seemed to be dependent on the relevant DS, HS and the period of stress exposure. Chlorophyll fluorescence was decreased in 50% volumetric water content (VWC) after 8 days of DS compared with the 100% VWC (control treatment). Leaf K and P content increased in moderate (50% VWC) irrigation stress and HS. Leaf hydrogen peroxide and lipid peroxidation increased after 8 days of DS, and this resulted in the increase of antioxidant enzymes activity. Overall, Maratheftiko performance against environmental stresses is related more to short-term DS than HS.
Keywords: Antioxidants; Climate change; Drought stress; Enzymes activity; Heat stress